Effects of Free-Choice Provision of Different Forage Sources in Preweaning Period on Performance and Some Rumen Parameters of Simmental Calves - Türkmen, M; Muruz, H (Journal of the Hellenic Veterinary Medical Society, 2023)
The objective was to evaluate the effect of free-choice provision of different forage sources [(alfalfa hay (AH) or grass hay (GH)] in preweaning period on performance and rumen fermentation of dairy calves. Twenty-one Individually housed Simmental calves (46.69 ± 4.14 birth weight, 3 days old) were randomly divided into 3 treatments of 7 calves each: Control: pelleted starter without forage, GH: pelleted starter + GH and AH: pelleted starter feed + AH. The study continued from 3 days of age to 56 days of age. All calves were fed 2 × 2.6 L of whole milk (5.2 L/day) until the end of the experiment. Starter and forage were offered ad libitum in different buckets during the experiment. Feed intake was monitored daily and body weight was measured at the begining and end of the experiment. Ruminal fluid samples were taken from calves on the last day of the experiment. Inclusion of forage in the diet had no significant effect on starter intake, final body weight, body structure, average daily gain (ADG) and feed conversion ratio. Fecal scores were also not affected by the treatments. At the end of the study, calves fed pelleted starter had lower rumen pH than calves fed forage supplemented diets (P<0.001). On the other hand, calves fed with forage-supplemented diets had higher acetate and acetate to propionate ratios than calves fed starter diets alone (P<0.01). The results of this experiment indicate that consumption of 5.74% GS and 6.60% AH of total DMI can improve the rumen environment without affecting starter feed consumption and animal performance, but If larger scale, on-farm studies confirm the results of this study, to achieve maximum growth in the preweaning period, it may be recommended to give the calves GH or AH separately from the starter feed.